Clinicopathological Characteristics and Molecular Phenotypes of Primary Hepatic Lymphoma - Xing, Ai-Yan; Dong, Xin-Zhe; Zhu, Liu-Qing; Liu, Long; Sun, Dong; Guo, Sen (Frontiers in Oncology, 2022)
Primary hepatic lymphoma (PHL) is a rare malignant tumor, occurring in 0.016% of non-Hodgkin’s lymphoma (NHL). The common histological subtype is diffuse large B-cell lymphoma (DLBCL). Due to the rarity of tumor, clinicopathological characteristics and molecular phenotypes of PHL are limited. Seven patients with PHL (primary liver DLBCL) and 13 cases of liver involvement by DLBCL diagnosed between 2014 and 2021 in our hospital were included. The genetic features were also compared between the two groups by next-generation sequencing (NGS). Differential gene expression and pathway enrichment analysis were also performed. There were some discrepancies on presenting symptoms, pathological characteristics, laboratory data, and prognosis between PHL and DLBCL-liver groups. No same mutation was found between PHL and DLBCL-liver groups by NGS. Differential gene expression analysis discovered some up- and downregulated genes in PHL compared with the DLBCL-liver group. Upregulated genes were enriched in metabolic pathways, and downregulated genes were enriched in the HTLV-1 infection pathway. PHL is a distinct entity, with unique molecular features compared to liver involvement of systemic lymphoma. Kaplan–Meier analysis showed that the prognosis of the PHL group was better than that of the DLBCL-liver group. Understanding the clinicopathological and molecular features of PHL would help to direct clinical treatment.